N‐Annulated perylene diimide dimers and tetramer non‐fullerene acceptors: impact of solvent processing additive on their thin film formation behavior. Issue 4 (2nd September 2021) - Laventure, Audrey; Stanzel, Samantha; Payne, Abby‐Jo; Lessard, Benoît H; Welch, Gregory C
Abstract: BACKGROUND: We aim to determine whether the rationale of designing a tetrameric non‐fullerene acceptor (NFA) to minimize its aggregation compared to its dimer counterparts proves to be a valid strategy in the context of organic photovoltaic (OPV) processing involving solvent additives. We investigate the impact of the molecular design and the processing additive on the thin film formation behavior of four N ‐annulated perylene diimide (NPDI x ) derivatives. We compare three dimers and a tetramer, processed from a solution containing 1, 8‐diiodooctane (DIO), which are used as NFAs and as a processing solvent additive, respectively, in the OPV fabrication. RESULTS: We prepared OPV devices using the PTB7‐Th:NPDI x model system and rationalized the change in their power conversion efficiency (PCE) based on the thin film morphology of the four NDPI x compounds. While the PCE of the OPV devices prepared using the dimers and 1% (v/v) DIO showed a 20–30% drop, those prepared using the tetramer and the same processing conditions showed an 80% drop. Our analysis demonstrates that DIO processing solvent additive‐induced crystallization of the tetramer is the cause of its low performance in OPV devices. CONCLUSION: Our results highlight that relying solely on the tetramer perylene diimide design strategy to prevent the aggregation observed in dimers is not always reliable when processing solvent additives are used in the OPV fabrication. Both the molecular design and the processing solvent additive impact the aggregation behavior of the NFA and need to be taken into account to optimize OPV devices active layer morphology. © 2021 Society of Chemical Industry